Espaces vacants et dégradation du cadre de vie dans une ville décroissante : le cas de Roubaix - Nadia Arab; Yoan Miot (Cybergeo, 2021)
While vacant spaces, both built and unbuilt, are considered to be one of the most striking urban manifestations of shrinking cities and participate in urban degradation, the nature and extent of the relationship between vacant spaces and living environment are rarely explored. The article proposes to examine this relationship based on a qualitative survey of users and a land survey in two districts of a shrinking French city : Roubaix. It gives an account of the way in which vacant spaces generate environmental and material disorders, strongly impacting the perception of the living environment. It also testifies to a set of indirect effects participating in the systemic degradation of the living environment. Thus, it goes beyond the conventional debates on the effects of vacant spaces on real estate value and the feeling of insecurity, by showing the existence of multiple effects and significant consequences on the users’ representations.